THE INFLUENCE OF STREAMER TRUSTWORTHINESS, PRICE DISCOUNTS, AND TIME PRESSURE ON IMPULSE BUYING BEHAVIOR IN TIKTOK LIVE STREAMING COMMERCE - DIA NUR AVITA SARI; KHANDI TUNGGA WIJAYA (SHACRAL: Shari'ah Economics Review Journal, 2026)
The rapid growth of TikTok Live Streaming Commerce has transformed consumer purchasing behavior, particularly by increasing the tendency toward impulse buying. This study aims to analyze the effects of streamer trustworthiness, discounted price, and time pressure on impulse buying behavior in TikTok Live Streaming Commerce among Muslim consumers. In addition, this study examines the moderating role of religiosity in the relationships between these variables and impulse buying behavior. A quantitative approach was employed using a survey method with purposive sampling. Data were collected from 200 Muslim consumers who had previously purchased products through TikTok Live Shopping and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that streamer trustworthiness, discounted price, and time pressure have positive and significant effects on impulse buying behavior. Furthermore, religiosity significantly weakens the effects of discounted price and time pressure on impulse buying behavior, indicating that higher levels of religiosity can reduce consumers’ susceptibility to promotional stimuli and urgency-driven purchases. However, religiosity does not significantly moderate the relationship between streamer trustworthiness and impulse buying behavior. These findings suggest that religiosity functions as an internal self-control mechanism that helps Muslim consumers avoid excessive and spontaneous purchasing behavior, particularly in response to price promotions and time-limited offers. This study contributes to the literature on digital consumer behavior and Islamic economics by providing empirical evidence regarding the role of religiosity in live streaming commerce.